A review of silicon-based aerogel thermal insulation materials: Performance optimization through composition and microstructure - Li, Chengdong; Chen, Zhaofeng; Dong, Weifu; Lin, Liangliang; Zhu, Xiangmiao; Liu, Qingsong; Zhang, Yue; Zhai, Ni; Zhou, Zihao; Wang, Yuhang; Chen, Baoming; Ji, Yuexin; et al. (Journal of non-crystalline solids, 2021)
•Design principles of silicon-based aerogel thermal insulation materials are introduced.•Performance optimization strategies of SA-TIMs are elaborated in detail.•Relationship between the composition and final properties of SA-TIMs is reported.•Five different microstructures composed of second phase materials and SA are reported.•Future research direction of SA-TIMs are analyzed according to their practical applications. Silicon-based aerogel (SA) has attracted increasingly more attention in the field of thermal insulation as its extraordinary properties such as ultralight, ultra-low thermal conductivity, and strong designability. However, SA thermal insulation materials (SA-TIMs) have several intrinsic defects such as low strength and poor toughness, which make their processing and handling difficult and restrict their practical applications. Composition optimization and microstructure reconstruction are the most convincing and effective strategies to improve their mechanical and thermal insulation properties, achieve more functions, and reduce cost. This review encompasses a complete survey of scientific achievements related to the two strategies, describing their characteristics, microstructures, and properties. The influence of different compositions and various assembly structures on the final properties of SA-TIMs is thoroughly reported. The main focus of this review is to point out the design principles of SA-TIMs and discuss the most promising development trends towards their widespread applications.